Da teoria à prática: os saberes das professoras de crianças de zero a três anos - Sarti, Hilda Lucia Cerminaro (2010)
This work analyzes the knowledge of teachers of children aged zero to three, examining their daily practices basis, in the context of a municipal early childhood education center in the city of São Paulo. The study was a research-action: it used observation video registers of four teachers daily routines, working with three groups of children, at four moments: stories telling, feeding, playing and contact with the families. The filmed registers were then commented by them, in individual interviews and in pairs, with the aim of getting their interpretations about the scenes and their explanations about the several sources of knowledge and experiences that based the observed practices. The several types of knowledge were perceived as adaptations, transformations and associations of theory with practice, using personal filters, in accordance with the concrete situations in the work place, having as background their professional and personal trajectory. The knowledge of the teachers are built, over time, from their life stories, their childhood memories, experiences including those as mothers, readings, courses, tastes, getting along together and observation of other professionals, knowledge of the child, contact with the families, reflections on and about the practice, availability to hear and to perceive children s needs and rhythms, in addition to the academic training. Such process is crossed by the complexity and emergence of day to day situations, when such knowledges are mobilized in order to adequately work with the child. The research concludes that, to be successful and to contribute to the improvement of small children s education, all public training policy must be based on the knowledge of the teachers work place, on their thoughts, speeches, needs and expectations, acknowledging their professional value, stimulating their protagonism as social actors and looking for ways to understand how they transform their knowledge in day to day practices, with children, their peers and families